Decoding the performance of a blend of metal-oxide nanoparticles in Eichhornia crassipes biodiesel at varying injection timing through the routes of thermodynamic analysis and statistical optimization - Jain, Akshay; Bora, Bhaskor Jyoti; Kumar, Rakesh; Sharma, Prabhakar; Paramasivam, Prabhu; Agbulut, Umit (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Biodiesel, known for its large cetane number, low pour point, and lower aromatics and sulfur content, has appeared as a promising alternative to diesel. This study focuses on testing the biodiesel extracted from Eichhornia Crassipes with TiO2 nanoparticles at 150 ppm concentration in a diesel engine. The experiment involved varying injection timings (ITs) of the biodiesel and nanoparticle blend, with three ITs of 20, 23, 25 and 280bTDC, and a standard IT of 230bTDC for diesel. The engine was tested at five different engine loads, ranging from 20 % to 100 %, with an increment of 20 % after each step. The experimentation was conducted at a constant an engine speed of 1500 rpm and a compression ratio of 17.5. The result showed an enhanced performance and a decreased emissions of carbon monoxide and hydrocarbons for 200bTDC of biodiesel and nanoparticle blend. However, the emission of nitrogen oxides increased for the same blend and IT of 200bTDC. The study suggests that using a 150 ppm concentration of TiO2 nanoparticles in Eichhornia Crassipes biodiesel could be an alternative to diesel for diesel engines when IT is set at 200bTDC. Further, the statistical optimization using RSM suggests that the engine load around 61 % and IT of 20 0bTDC gives optimum values of response variables.
Keywords: Injection timing; Energy; Exergy; Efficiency; Emission; LIFE-CYCLE ASSESSMENT; DIESEL-ENGINE; WATER HYACINTH; FUEL; COMBUSTION; MICROALGAE; Thermodynamics; Energy & Fuels